Exposure to Contagion: Perceived Risks and Travel Behavioural Shifts in Malaysia during COVID-19 Pandemic - Md Yusuf, Mazlynda; Azhar, Nur Liyana Aqilah (Malaysian Journal of Science Health & Technology, 2021)
At the beginning of March 2020, the Coronavirus pandemic was acknowledged as a great confrontation that shook the travel organisations’ core. Indeed, it provides such a profound disturbance to the industry. It gives a preview of Malaysian travellers’ discernments in a distinctive point of time - the times of the COVID-19 linked to the worldwide lockdown and restriction movement order. Therefore, this study examines the relationship between perceived risks and Malaysian travel behaviour due to the COVID-19 pandemic and identifies the risk factors that influenced Malaysian travel behaviour. This study was focused on a random sampling among Malaysians who had experienced the pleasure of travelling. The questionnaire was designed to measure travel behaviour and several perceived risks, including travel, psychological, safety, security, financial, and health. Ordered Probit regression and test statistic scores disclosed that perceived psychological risk, perceived financial risk, and perceived health risk significantly impacted and positively correlated to Malaysian travelling behaviours due to COVID-19. The perceived risk factors further showed that anxious feelings existed to enjoy travelling during the pandemic. It shows that Malaysians travel behavioural had shifted due to the COVID-19 outbreak.